Sidoarjo Mudflow Electric (SMF-E): Optimalization of Sidoarjo Mudflow as an Electric Supplier Based on Electrochemical - Deni Ainur Rokhim (Universitas Muhammadiyah Sidoarjo, 2020)
Sidoarjo mudflow or known as Lusi (Lumpur Sidoarjo) is an ecological disaster that has caused the community fret. Most of them haven’t known that the mud contains elements that can produce electricity. This research aims to find the basic value that can be obtained from ecological disaster. The research design uses electrochemical method development with magnesium and copper electrodes. The result of the electric power that can be generated is 7,07135 watt/hour. It can reach an area of 4.405986 km2 or as wide as one residential in an electric production plant. The use of Lusi is very effective because it contains high metal and high salt content. The abundant amount of Lusi can be utilized effectively throughout this way